Teachers Questioning Strategies to Enhance Students’ Concentration in English Classes at Tenth Grade of SMA PGRI 2 Kota Jambi Academic Year 2017/2018 - Desiyana Rizqi Annisa, Suyadi, Yanti Ismiyati (JELT: Journal of English Language Teaching, 2018)
AbstractThis study aim to find how the teacher’s questioning strategies enhance students’ concentration at X grade SMA PGRI 2 Jambi academic year 2017/2018. The design of this research is experimental design type one group pretest and posttest design, ie only take one experiment class without control class or comparator class. Subjects in this study were students X IPS 3 which amounted to 35 peoples and an English teacher who teaches class X IPS 3 SMA PGRI 2 Jambi. While the object in this study is the concentration of students before and after treatment. To find out the concentration of students, the students' behavior was observed at the pretest and posttest. Then the data that has been collected will be analyzed statistically descriptive, after that interpreted quantitative by comparing the result before given treatment and after given treatment. The data will tested with Mann-Whitney U Test formula to make the conclusion.From this study found that the increased concentration of students after treatment. Before being given treatment, the concentration of students was 35.5% and after being given treatment the concentration of students increased to 62.55%. And the statistic result of Mann-Whitney U Test the hypotesis is accepted.Keywords: Teacher’s Questioning Strategies, Students’ Concentration, English Class